The extent of extrathyroidal extension is a key determinant of prognosis in T4a papillary thyroid cancer. Issue 6 (26th August 2019) - Abraham, Earl; Roshan, David; Tran, Bryan; Wykes, James; Campbell, Peter; Ebrahimi, Ardalan
Abstract: Background and Objectives: In papillary thyroid cancer (PTC), the adverse prognostic impact of extrathyroidal extension (macro‐ETE) invading the subcutaneous soft tissues, larynx, trachea, esophagus, or recurrent laryngeal nerve (T4a disease) is well established. We investigated whether the extent of macro‐ETE, defined as "limited" with single structure involvement (lim‐ETE) and "extensive" with multiple structures involved (ext‐ETE), influences prognosis in T4a PTC. Methods: A retrospective analysis of 610 patients with PTC identified 39 with T4a disease, including 26 with lim‐ETE and 13 with ext‐ETE. Univariate Cox regression was used to assess the relationship between the extent of macro‐ETE and recurrence‐free survival (RFS). Results: Ext‐ETE was associated with a five times increased risk of recurrence compared to lim‐ETE (HR 5.0, P < .030), with or without adjustment for radioactive iodine administration and after adjustment for margin status (HR 4.7; P = .041). A low‐risk subset of T4a disease comprising of patients aged less than 55 years with lim‐ETE and clear margins accounted for one‐third of the cohort and demonstrated an excellent 5‐year RFS of 92%. Conclusions: The extent of macro‐ETE appears to be an important determinant of prognosis in T4a PTC. A low‐risk subset of T4a disease exists with an excellent prognosis.